Two Questions for Wolterstorff: On the Roles Played by Rights-Talk in History and the Measuring of Worth - Perry, John (Studies in Christian ethics, 2010)
Much of Nicholas Wolterstorff’s argument in Justice: Rights and Wrongs is persuasive and helpful, especially his focus on perceiving instances of injustice as wronging, i.e., the denial of the goods to which one has a right. Two aspects of his theory are less persuasive, one historical and one theoretical. Historically, although he convincingly shows that the concept of rights is much older than some claim, he does not account for how the function of rights-talk may have changed. Theoretically, his account of worth seems undeveloped. Worthy art or worthy philosophy papers or worthy acts of love have different rights than unworthy such objects. But how is such worth measured? It would seem that the standard of excellence appropriate to each object does at least part of the work in generating the right, thus suggesting that rights are not generated by worth alone, as Wolterstorff implies.